2017
DOI: 10.1159/000477327
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Inhibits Hypoxia–Induced Epithelial-To-Mesenchymal Transition via Upregulation of miR-200b in HK-2 Cells

Abstract: Background/Aims: Renal tubular epithelial-mesenchymal transition (EMT) is regarded as an important factor leading to renal interstitial fibrosis. Erythropoietin (EPO) has been reported to attenuate renal fibrosis. The mechanism underlying this protective effect of EPO remains unclear. In this study, we aim to identify possible mechanisms of the EPO renoprotective effect. Methods: Hypoxia was induced in vitro by incubating human proximal tubular epithelial cell line HK-2 cells in 1% O2 and 5% CO Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…These alterations were accompanied with a notably increased expression of mesenchymal markers (α-SMA, collagen I, FSP-1 and vimentin), and a decreased expression of E-cadherin. These results are in agreement with previous studies (35)(36)(37). Interestingly, BMP-7 overexpression prevented this transformation from an epithelial to mesenchymal phenotype when treated with TGF-β1.…”
Section: Discussionsupporting
confidence: 93%
“…These alterations were accompanied with a notably increased expression of mesenchymal markers (α-SMA, collagen I, FSP-1 and vimentin), and a decreased expression of E-cadherin. These results are in agreement with previous studies (35)(36)(37). Interestingly, BMP-7 overexpression prevented this transformation from an epithelial to mesenchymal phenotype when treated with TGF-β1.…”
Section: Discussionsupporting
confidence: 93%
“…Thus hypoxia‐induced HK‐2 cell is often used to imitate the pathological process of renal interstitial fibrosis in vitro 20, 21. The data revealed that the cell viability was significantly decreased and the LDH release was greatly increased in hypoxia‐induced HK‐2 cells as compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that EPO has cytoprotective effects in many non-erythroid cells, including renal TECs, which are largely attributed to anti-apoptosis, anti-oxidant, and anti-in ammatory effects [42]. Moreover, EPO has been shown to upregulate miR-200 expression and attenuate hypoxia-induced EMT in HK-2 cells [43] as well as counteract TGF-β1-induced EMT by regulating TGF-β/Smad-2 signaling and inhibit renal brosis in UUO kidneys [15]. Unfortunately, repetitive high dose rhEPO treatments were required to achieve these bene ts, which would translate to ~210,000 U in a 70-kg patient, approximately 10 times the dose normally administered to patients with severe renal anemia.…”
Section: Discussionmentioning
confidence: 99%